Budgetary Slack: Iklim Kerja Etis, Motivasi Berprestasi, Komitmen Organisasi, dan Modal Intelektual - Putri, Rizki Sari Eka; Firmansyah, Amrie (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2022)
Better work performance compared to the ability to absorb the budget indicates that the output can be achieved with a lower budget allocation than the planned budget. This illustrates that the budget available to Ministries/Agencies is larger than it should be. Based on these conditions, the research was conducted with the aim of examining the effect of ethical work climate, need for-achievement and organizational commitment of budgetary slack moderated by intellectual capital with the research locus at the Ministry of Home Affairs. The study applied quantitative method with a sample of 137 civil servants who were determined purposively. Research data analysis used the Structural Equation Modelling with hypothesis testing based on path analysis. The results of the study found that an ethical work climate had no effect on budgetary slack, while need for-achievement and organizational commitment had a significant positive effect on budgetary slack. Intellectual capital proved unable to moderate the relationship of the three variables to budgetary slack. Performa kinerja yang lebih baik dibandingkan dengan kemampuan penyerapan anggaran mengindikasikan bahwa keluaran (output) dapat dicapai dengan alokasi anggaran yang lebih rendah dari anggaran yang telah direncanakan. Hal ini menggambarkan bahwa anggaran yang tersedia pada Kementerian/Lembaga lebih besar dibandingkan yang seharusnya. Penelitian dilakukan pada tahun 2021 untuk mengkaji pengaruh iklim kerja etis, motivasi berprestasi dan komitmen organisasi terhadap budgterary slack yang dimoderasi oleh modal intelektual dengan lokus penelitian pada Kementerian Dalam Negeri. Penelitian menerapkan metode kuantitatif dengan sampel sebanyak 137 pegawai negeri sipil yang ditentukan secara purposive. Analisis data penelitian menggunakan Structural Equation Modelling dengan pengujian hipotesis berdasarkan jalur analisis. Hasil penelitian menemukan bahwa iklim kerja etis tidak berpengaruh terhadap budgetary slack, sedangkan motivasi berprestasi dan komitmen organisasi berpengaruh positif signifikan terhadap budgetary slack. Modal intelektual terbukti tidak mampu memoderasi hubungan ketiga variabel terhadap budgetary slack.